Metformin and its use in chronic kidney disease, cardiovascular disease and cancer. Issue 2 (February 2015) - Sultana, Ramona-Rita; Rice, Sam
Metformin is nowadays considered to be the first-line pharmaceutical agent in type 2 diabetes mellitus (T2DM). When used as monotherapy, it can reduce the glycosylated haemoglobin (HbA1c ) level by up to 12 mmol/mol; a property that is not seen in many of the newer anti-diabetic agents. It also has the advantage of reducing the risk of cardiovascular disease in patients with T2DM when compared with sulfonylureas and insulin. Metformin is not recommended in patients with degrees of renal impairment and there is a lack of guidelines on the use of metformin in patients with stable chronic kidney disease.